THE INFLUENCE OF ASSETS, NON-PERFORMING LOANS (NPL), ALLOWANCE FOR IMPAIRMENT LOSSES (PYD), AND THIRD-PARTY FUNDS (DPK) ON THE NUMBER OF KB BANK OFFICES OVER THE 2021–2025 PERIOD. - Ami Nullah Marlis Tanjung; M. Guffar Harahap (INTERNATIONAL, Journal of Sharia Business Management, 2026)
This study aims to examine the influence of financial performance indicators on both the physical branch network and financing distribution at KB Bank Indonesia. Specifically, it investigates the effect of Assets, Non-Performing Loans (NPL), Allowance for Impairment Losses (PYD), and Third-Party Funds (DPK) on the number of bank offices over the 2021–2025 period, as well as the impact of Non-Performing Financing (NPF) and Net Income (NI) on financing disbursement during the 2023–2025 period. This research employs a quantitative associative approach, utilizing secondary data derived from the bank's published financial reports. Data analysis was conducted using SPSS, encompassing validity and reliability tests, classical assumption tests (normality, multicollinearity, linearity, and heteroscedasticity), multiple linear regression, and hypothesis testing (t-test and F-test). The findings reveal that the number of KB Bank offices declined consistently from 352 in 2021 to 150 in 2025; however, this downward trend was not uniformly accompanied by deterioration in financial indicators, as certain years witnessed simultaneous office reductions with asset growth and improved credit ratios. This suggests that branch rationalization decisions are driven more by digital transformation and operational efficiency strategies than by a deterministic financial formula. Furthermore, the regression analysis demonstrates that NPF and NI jointly explain 99.7% (R²) of the variation in financing distribution. Partially, NPF exerts a positive and significant effect on financing (t-count 6.546 > 2.056; sig. 0.000 < 0.05), whereas NI exhibits a negative and insignificant effect (t-count -0.553 < 2.056; sig. 0.655 > 0.05), indicating that increased profitability does not automatically translate into credit expansion. The F-test confirms the simultaneous significance of both variables (F-count 1605.499 > 3.39; sig. 0.000 < 0.05). In conclusion, the relationship between financial indicators and banking strategies is asymmetric and highly contextual, underscoring the shift from physical expansion toward digital optimization. While KB Bank Syariah demonstrates operational effectiveness in asset management and intermediation, stringent risk management remains imperative. For regulators, these findings highlight the necessity of balancing digital transformation policies with sustained financial inclusion, particularly in underserved regions. Future research is encouraged to incorporate moderating variables such as interest rates, inflation, or technology adoption indices to attain a more comprehensive understanding.